2019
DOI: 10.1007/s40199-019-00261-8
|View full text |Cite
|
Sign up to set email alerts
|

Genus Sideritis, section Empedoclia in southeastern Europe and Turkey – studies in ethnopharmacology and recent progress of biological activities

Abstract: Background Over the last two decades there has been a substantial increase of the number of studies on the species of genus Sideritis. Species of section Empedoclia, occurring in the Eastern Mediterranean region and in part of Western Asia possess some remarkable characteristics and are known as valuable medicinal plants used by local people in the traditional medicine and for herbal tea. The objective of the review is to make a survey on the recent studies on the ethnopharmacology and biological activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 116 publications
0
36
0
Order By: Relevance
“…Genus Sideritis is very rich in flavonoid derivatives [45][46][47]. In this study, twelve flavonoid analogues were isolated which were categorized into one 3-hydroxyflavone (7), one flavone (8), one flavone 7-O-glucoside (9), four flavone 7-O-p-coumaroyl-glucosides (10-13) and five flavone 7-O-allosylglucosides (14)(15)(16)(17)(18).…”
Section: Phytochemical Contentmentioning
confidence: 99%
“…Genus Sideritis is very rich in flavonoid derivatives [45][46][47]. In this study, twelve flavonoid analogues were isolated which were categorized into one 3-hydroxyflavone (7), one flavone (8), one flavone 7-O-glucoside (9), four flavone 7-O-p-coumaroyl-glucosides (10-13) and five flavone 7-O-allosylglucosides (14)(15)(16)(17)(18).…”
Section: Phytochemical Contentmentioning
confidence: 99%
“…Species of the genus Sideritis L. (Lamiaceae) belonging to the section Empedoclea are widely distributed in the Eastern Mediterranean, Italy, Balkan Peninsula and Asia Minor [1] and occur mainly in Turkey [2–4] . In Cyprus, three Sideritis species ( S. perfoliata L., S. cypria Post, S. curvidens Stapf.)…”
Section: Introductionmentioning
confidence: 99%
“…; and Sideritis syriaca L., has been listed by European Medicine Agency (EMA) as a traditional medicine for the relief of mild gastrointestinal discomfort and against the common cold (EMA, 2015). Previous detailed studies underlie the important pharmacological activities of the genus such as the antioxidant, anti-inflammatory, antivirus, anticancer, hepatoprotective, antispasmodic, analgesic, neuroprotective activity, as well as its great effectiveness against diseases related to the central nervous and to the urinary system (Kirimer et al, 2004;Gonzaĺez-Burgos et al, 2011;EMA, 2015;Hofrichter et al, 2016;Deveci et al, 2017;Aneva et al, 2019). Indeed, a clinical study that carried out by Wightman et al (2018), showed that S. scardica (Greek mountain tea) improved the aspects of cognitive function and mood in a group of healthy, older adults.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Sideritis L. comprises around 150 species (Aneva et al, 2019); among them, the endemic species S. cypria Post. is a perennial herb belonging to the section Empedoclia Rafin., 60 cm high with bright yellow flowers, growing at altitude 300-925 m in Pentadactylos Mountains in Northern Cyprus (Meikle, 1985;Yildiz and Gücel, 2006;Tsintides et al, 2007).…”
Section: Introductionmentioning
confidence: 99%